Empowering Women-Fashion SMEs: Dynamic Capabilities, Agility, and Resilience - Prihartono, Budhi; Maulidan, Rahmat; Zulfatri, Muthi Maitsa; Damayanti, Annisa Rizqi (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2025)
Abstract: This study investigates how digital transformation enhances organizational resilience in women’s fashion SMEs through the roles of digital transformation, innovation capability and organizational agility, grounded in Dynamic Capabilities Theory. Utilizing non-probability purposive sampling, data were collected from 92 SMEs in the Jabodetabek region and analyzed via SEM-PLS and SPSS 15.0. Findings indicate that digital transformation significantly strengthens innovation capability and directly enhances organizational resilience, though it does not significantly affect organizational agility. Innovation capability emerges as a robust predictor of both organizational agility and resilience, while agility itself directly contributes to resilience. The study extends Dynamic Capabilities Theory to resource-constrained creative-sector SMEs in developing economies, demonstrating their capacity to cultivate strategic capabilities amid turbulence. It addresses a critical gap in the literature by empirically examining the interplay among digital transformation, innovation capability, agility, and resilience within an SME context. Practical implications suggest that support institutions, business coaches, and policymakers can leverage this model to design targeted development programs that foster adaptive, proactive, and resilient SMEs capable of navigating uncertainties such as volatile consumer demand, economic instability, and digital disruption